PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KREATIFITAS SISWA - Azuai, Laili; D, Hamidah; Puspita, Manda (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
This research aims to provide freedom for students to explore themes or parts of the project so that students can develop ideas according to their interests. This can hone students' abilities in critical thinking, collaboration and innovation. This research applies a quantitative approach based on literature studies which were previously documented in journals and books to provide data sources for research. The research results show that the application of the project-based learning model (Project Based Learning, PBL) has proven effective in increasing student creativity at various levels of education. This model includes learning processes and end results that involve students actively designing and implementing real projects.